Pengaruh Kualitas Pelayanan dan Persepsi Harga terhadap Kepuasan Konsumen Dzikra Laudry Kota Tasikmalaya - Azis Azis; Cece Rakhmat; Rita Tri Yusnita (ULIL ALBAB : Jurnal Ilmiah Multidisiplin, 2022)
The purpose of this study was to determine and analyze the effect of service quality and price perception on consumer sastisfaction of Dzikra Laundry in Tasikmalaya City. The research method used is a survey method with data obtaibed directly through a questionnaire to 100 responden taken from the consumer Dzikra Laundry. The technique used is multiple regression. Based on the results of this study, it is known that there is a simultaneous significan effect between service quality partially has a price perception on consumer satisfaction and price perception partially has a signifiacan effect on consumer satisfaction decisions Dzikra Laundry in Tasikmalaya City.